2015
DOI: 10.1002/sej.1205
|View full text |Cite
|
Sign up to set email alerts
|

A Theoretical Analysis of the Role of Characteristics in Entrepreneurial Propensity

Abstract: Research summary:The literature reveals a broad range of inconsistencies in defining entrepreneurship and in identifying personal characteristics that predict and explain the phenomena of entrepreneurship. The purpose of this work is to propose a model for consistency in predicting entrepreneurial propensity. This article acknowledges categories of entrepreneurs such as: business enterprise creating entrepreneurs, social entrepreneurs, student entrepreneurs, academic entrepreneurs, and corporate entrepreneurs.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
31
0
3

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 46 publications
(34 citation statements)
references
References 42 publications
0
31
0
3
Order By: Relevance
“…Prior studies found that entrepreneurs work longer hours and harder (Bhide, 1996; Blanchflower, 2004; Chay, 1993; Eden, 1973; Hamermesh, 1990; Hofer, 1976; Levesque & Minniti, 2006; Van Ness & Seifert, 2016). Hedonism is defined as pleasure and sensuous gratification for oneself (Schwartz, 2015), which is the opposite of high level of work effort associated with entrepreneurship (Looi, 2017).…”
Section: Review Of Literaturementioning
confidence: 99%
“…Prior studies found that entrepreneurs work longer hours and harder (Bhide, 1996; Blanchflower, 2004; Chay, 1993; Eden, 1973; Hamermesh, 1990; Hofer, 1976; Levesque & Minniti, 2006; Van Ness & Seifert, 2016). Hedonism is defined as pleasure and sensuous gratification for oneself (Schwartz, 2015), which is the opposite of high level of work effort associated with entrepreneurship (Looi, 2017).…”
Section: Review Of Literaturementioning
confidence: 99%
“…Entrepreneurs are at the center of venture creation and growth, and, so, their characteristics that lead to venture success have been studied thoroughly for over 50 years (Ács and Audretsch, 2003;Barkham, 1994;Brandstätter, 2011;Roper, 1998;Unger et al, 2011;Van Ness and Seifert, 2016;Zhao and Seibert, 2006). Along with the psychological traits of entrepreneurs (Zhao et al, 2010), entrepreneurs' skill sets have been highlighted as critical to their success (Chell, 2013;Crook et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Entrepreneurs may need to work long hours, sometimes for weeks or years before achieving objectives (Van Ness & Seifert, 2016). The willingness to delay gratification is thought to be reinforced by a passion for one’s work and it is perceived as a core characteristic of entrepreneurs (Baum et al, 2004, p. 590).…”
Section: Gratification Delaymentioning
confidence: 99%